KEANEKARAGAMAN JENIS IKAN DI DANAU TAMAN WISATA ALAM BULUHCINA SEBAGAI RANCANGAN MODUL PADA MATERI KEANEKARAGAMAN HAYATI DI SMA KELAS X - Kholiq, Abdul; Yustina, Yustina; Ahmad, Darmadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This research was conducted to determine the diversity of fish species in the Lake of Taman Wisatan Alam Buluhcina and to design a biodiversity concept module on class X biodiversity material in April 2019 - July 2019. This research was carried out in 2 stages, namely the stage of field data collection, and the module design stage . The first stage was carried out at 4 observation sites in the Buluhcina Nature Tourism Park. Research using survey methods. Determination of the location of research carried out by purposive sampling. Sampling of fish is done by using fishing gear in the form of fishing nets, fishing rods, pillars at each station, three times repetition is taken, ie the catching device is installed and taken in the morning at 07.00-08.00 and in the afternoon at 16.30-17.30. The second stage of module design uses the ADDIE development model. the highest number of species at station IV was around 164 individuals, then station II with a total of 115 individuals and at station I there were 110 individuals and station III with the least number of 73 individuals with the total number of stations totaling 462 individuals. The index value of diversity, uniformity and dominance of fish species found in Oxbow Lake in Buluhcina natural tourism park at each station. The species diversity index value (H ') is around 2.39, the species uniformity index value (E) is around 0.86 and the species dominance index value (C) is around 2.58. The results of the study can be used as a source of high school biodiversity class X module designKey Words: Fish species diversity, lake, module.